Assessing and promoting partnership between patients and health-care professionals: Co-construction of the CADICEE tool for patients and their relatives - Pomey, Marie-Pascale; Clavel, Nathalie; Normandin, Louise; Grande, Claudio Del; Ghadiri, Djahanchah Philip; Fernandez-McAuley, Isabel; Boivin, Antoine; Flora, Luigi; Janvier, Annie; Karazivan, Philippe; Pelletier, Jean-François; Fernandez, Nicolas; et al. (Health Expectations, 2021)
Context Partnership between patients and health-care professionals (HCPs) is a concept that needs a valid, practical measure to facilitate its use by patients and HCPs. Objective To co-construct a tool for measuring the degree of partnership between patients and HCPs. Design The CADICEE tool was developed in four steps: (1) generate key dimensions of patient partnership in clinical care; (2) co-construct the tool; (3) assess face and content validity from patients’ and HCPs’ viewpoints; and (4) assess the usability of the tool and explore its measurement performance. Results The CADICEE tool comprises 24 items under 7 dimensions: 1) relationship of Confidence or trust between the patient and the HCPs; 2) patient Autonomy; 3) patient participation in Decisions related to care; 4) shared Information on patient health status or care; 5) patient personal Context; 6) Empathy; and 7) recognition of Expertise. Assessment of the tool's usability and measurement performance showed, in a convenience sample of 246 patients and relatives, high face validity, acceptability and relevance for both patients and HCPs, as well as good construct validity. Conclusions The CADICEE tool is developed in co-construction with patients to evaluate the degree of partnership in care desired by patients in their relationship with HCPs. The tool can be used in various clinical contexts and in different health-care settings. Patient or Public Contribution Patients were involved in determining the importance of constructing this questionnaire. They co-constructed it, pre-tested it and were part of the entire questionnaire development process. Three patients participated in the writing of the article.
Number: 4 _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/hex.13253
Keywords: Co-création; Libre accès; Partenariat; Partenariat avec le patient; Publication UdeM